HUBUNGAN KEPIMPINAN PENGAJARAN MAYA TERHADAP KOMPETENSI PENGAJARAN GURU (Proceeding 7th International Seminar on Regional Education, 2015)
abstractEffective instructional leader was identified as a key factor for school effectiveness.School leaders should pay full commitment to improve the quality of teaching and learning in the classroom. This study was conducted to identify the effect of virtual instructional leadership practices toward teaching competency among school teachers. Data were collected through questionnaires from 352 respondents and analyzed using SEM. The result shown all the three dimensions that was suggested for the virtual instructional leadership were significant with the loading factor in range 0.41 and 0.98, while all dimensions that was suggested for teaching competency also significant with loading factor between 0.40 and 0.84. Beside that, the finding also shown that virtual instructional leadership contributed significantly toward teaching competency guru (Î²= 0.427, C.R = 6.758, P = .000). Finally, the study was successfull developed an interactional model between virtual instructional leadership and teaching (Ï2=1928.732, dk=926, P= <0.05)..Keywords: instructional leadership, teaching competency, mobile technology.